How to be a Good Teacher: Passion, Person, and Pedagogy. Issue 2 (2nd April 2016) - Benekos, Peter J.
Abstract : What makes a good teacher? What are the characteristics and qualities that distinguish a good teacher? How does a good teacher teach? Can teachers learn to be more effective? These questions reflect efforts to define teaching excellence and to identify strategies that improve teaching. Researchers have developed lists, models, and taxonomies that identify both personal traits and pedagogical skills that contribute to effective teaching and distinguish good teachers. Findings support that good teachers have engaging personality, knowledge, and pedagogical skills that are demonstrated with passion and enthusiasm. This article reviews perspectives on good teaching, presents observations on what is a good teacher, and concludes with reflections and questions that can provide a framework to critique how to be a good teacher.